2014
DOI: 10.1080/13607863.2014.948805
|View full text |Cite
|
Sign up to set email alerts
|

Social capital and depression: evidence from urban elderly in China

Abstract: This study provides new evidence that social capital effectively mediates geriatric depression directly and indirectly. The intervention of social capital on depression should therefore consider the two pathways. Future longitudinal studies should help further understand the mechanisms linking social capital and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
136
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(157 citation statements)
references
References 51 publications
17
136
4
Order By: Relevance
“…We found that a higher level of social capital was associated with a lower likelihood of experiencing depressive disorders after adjustment for confounders in the total population, which is consistent with previous studies [6,10,11,27]. Li et al [10] and Han et al [6] showed that a lower level of social capital (concerning trust and reciprocity) was connected associated with suffering from depression among people in their later life.…”
Section: Discussionsupporting
confidence: 91%
“…We found that a higher level of social capital was associated with a lower likelihood of experiencing depressive disorders after adjustment for confounders in the total population, which is consistent with previous studies [6,10,11,27]. Li et al [10] and Han et al [6] showed that a lower level of social capital (concerning trust and reciprocity) was connected associated with suffering from depression among people in their later life.…”
Section: Discussionsupporting
confidence: 91%
“…Social capital is observed to improve health status (e.g., Yamamura 2011, Fiorillo andSabatini 2015). Cao et al (2015) used individual-level data from urban China to show that trust was significantly associated with geriatric depression, although social participation was not correlated with geriatric depression. In contrast, in Nordic countries a trust in neighbors failed to show a significant association with depression for adults over 65 years of age (Forsman et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For both BADL and IADL, the respondents' responses were scored as: I don't have any difficulty = 4, I have difficulty but can still do it = 3, I have difficulty and need help = 2, I cannot do it = 1. The scores were summed up and defined as BADL (range: 6-24) and IADL (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The Chronbach's α was 0.…”
Section: Activities Of Daily Living (Adl)mentioning
confidence: 99%
“…Compared to studies on the issue in developed countries, China's studies have been relatively scarce and provide mixed results. Studies have found that social network and social capital-which are concepts closely related to and overlapped with SP-were positively associated with health outcomes [16][17][18][19], whereas one study found no association between social capital and geriatric depression [20]. Regarding SP, studies have shown conflicting evidences; SP was found to improve self-rated health (SRH) and mental health but have no effect on chronic diseases [21], whereas an inverse association between SP and the onset of hypertension was found for women but not for men [22].…”
Section: Introductionmentioning
confidence: 97%